Penegakan Hukum Terhadap Pelanggaran Hak Cipta Dalam Jual Beli Karya Sastra Pada Marketplace - Ratih Widowati (Universitas Pendidikan Nasional, 2022)
The large number of book piracy and/or unauthorized sellers in the marketplace is a serious legal problem. Book piracy has become an industry in Indonesia. This is due to the lack of law enforcement that occurs, consumer behavior that is not aware of copyright, and business actors who seek profit by illegal means. Business actors in this case are not only sellers, but also the marketplace as a digital trading platform provider should also be responsible for selecting the goods to be sold by the seller. Unfortunately, the focus of law enforcement on copyright infringements is still focused only on piracy actors. Marketplace providers as an important element in digital transactions often not charged with legal responsibility. Therefore, this study focuses on how the responsibility of the marketplace and the mechanism for resolving copyright disputes that occur in the marketplace. This research uses normative legal research methods. The results of this study indicate that there is an agreement between the seller/partner/merchant and the marketplace as a digital trading platform provider. From this agreement, the elements of Article 10 of the Indonesia Copyright that state “Managers of business premises are prohibited from allowing the sale and/or reproduction of goods resulted from Copyrights and/or Related Rights infringements in the location under their management.” The dispute resolution mechanism regulated in the Copyright Law consists of litigation (civil and criminal) and non-litigation.